ANÁLISIS A LOS ESTADOS FINANCIEROS DE LA COOPERATIVA DE AHORRO Y CRÉDITO “29 DE ENERO CHAGUARPAMBA” DEL CANTÓN CHAGUARPAMBA, PERIODO 2016-2017” - Córdova Guevara, Gabriela Elizabeth (2019)
This thesis entitled "ANALYSIS TO THE FINANCIAL STATEMENTS OF THE credit union" JANUARY 29 CHAGUARPAMBA "CHAGUARPAMBA CANTON, Period 2016-2017" was developed in order to comply with the objectives, whose purpose is to know the real economic and financial situation of the entity. The methodology applied allowed the analysis of the financial statements of the cooperative, in order to provide adequate information for decision-making, so the vertical analysis was elaborated to know the percentage participation that each account has with respect to the group to which belongs, determining the composition and structure of the financial statements analyzed. In addition, the horizontal analysis was carried out to establish the existing variations, which refer to the increases and decreases that have been made in the amounts of the accounts of the financial statements of the 2016-2017 economic periods. Subsequently, the financial indicators established by the Superintendence of Popular and Solidarity Economy (SEPS) were applied; and, finally, the final financial report of the results of the information analyzed is prepared and argued, as well as conclusions and recommendations that contribute to the correct decision making by the managers and administrators of the 5 financial institution. At the conclusion of the present work, it can be seen that in Cooperativa 29 de Enero Chaguarpamba, there is an excess of unproductive assets in the entity, reflecting that the cooperative is not being efficient in the allocation of resources in productive assets that generate income, demonstrating a inadequate administration in it; it has a high delinquency rate of the portfolio, therefore attention must be paid when evaluating the payment capacity of the partners, the coverage of the unproductive portfolio is very low, which could cause large economic losses. The cooperative has liquidity which indicates that the entity can meet its short-term obligations at the time the partners request to have their monetary resources.